The Costs of Substitution - von Weizsacker, C. Christian (Econometrica, 1984)
[The lecture investigates some consequences of a frequently observed phenomenon: There are once and for all costs of switching from one good to one of its substitutes. The decision to substitute then is an investment decision. Such substitution costs, in conjunction with problems of oppportunism, have frequently been seen as a reason for vertical integration. Reputation for a fair treatment of customers may enable suppliers to maintain market relations for goods involving substitution costs. A model looks at "competitive distance" between two goods with substitution costs. If future tastes are uncertain the model shows that with low rates of discount or high rates of market growth competitive distance declines as substitution costs rise. It is also shown that competitive distance rises with a rising rate of discount. Given the effectiveness of the reputation mechanism, numerical analysis shows that competitive distance is smaller in most cases with substitution costs than without substitution costs.]